2011
DOI: 10.30770/2572-1852-97.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Physicians Reentering Clinical Practice: Characteristics and Clinical Abilities

Abstract: INTRODUCTION: Limited information exists to describe physicians who return to practice after absences from patient care. The Center for Personalized Education for Physicians (CPEP) is an independent, not-for-profit organization that provides clinical competency assessment and educational programs for physicians, including those reentering practice. This article studies the medical licensure status, performance and correlates between physician characteristics and performance on initial assessment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…A recent study of 62 physicians who voluntarily left practice and subsequently had their clinical skills evaluated found the average age of the participants to be 53.7 years. 37 Given the rate of change of the vital knowledge to safely and effectively practice as a health care professional, as well as the preceding discussion of continuing competency, there are concerns that such professionals may not be prepared to resume practice. Grace et al found that, of re-entering physicians who completed a clinical skills evaluation, "the majority (67%) were found to have educational needs requiring moderate to considerable reeducation or updating, and another 6.5% showed educational needs that were broad enough to recommend education in a residency program to prepare for a return to practice."…”
Section: Mid-career Practicementioning
confidence: 99%
“…A recent study of 62 physicians who voluntarily left practice and subsequently had their clinical skills evaluated found the average age of the participants to be 53.7 years. 37 Given the rate of change of the vital knowledge to safely and effectively practice as a health care professional, as well as the preceding discussion of continuing competency, there are concerns that such professionals may not be prepared to resume practice. Grace et al found that, of re-entering physicians who completed a clinical skills evaluation, "the majority (67%) were found to have educational needs requiring moderate to considerable reeducation or updating, and another 6.5% showed educational needs that were broad enough to recommend education in a residency program to prepare for a return to practice."…”
Section: Mid-career Practicementioning
confidence: 99%
“…The Academy of Medical Royal Colleges (AoMRC) has found that ‘whilst there is little shortage of opinion in this area, there is little clear evidence’ [ 3 ]. An observational study of 62 doctors from the United States found that the majority (67%) of doctors who had been absent from practice for 18 months or more ‘were found to have educational needs requiring moderate to considerable re-education or training ... many re-entering physicians may not be ready to jump back into practice’ [ 4 ]. In 2017, Health Education England (HEE) conducted a survey of trainees and employers via the HEE Deans, the British Medical Association the AoMRC, research bodies, the NHS Improvement and NHS England medical directors, and chief professional officers.…”
Section: Introductionmentioning
confidence: 99%
“…A 2002 JAMA review of the topic cited caretaking responsibilities, personal illness, career dissatisfaction, and alternative careers as common causes of physician reentry 1 . More recent studies suggest that changes in career paths into a non‐clinical position (such as administration), family issues, military deployments, and career dissatisfaction also contribute to physicians leaving the workforce voluntarily 8,12–13,15 . A survey of over 6000 pediatricians younger than 65 found that 12% of respondents indicated they had experienced a period of clinical inactivity lasting >12 months.…”
Section: Introductionmentioning
confidence: 99%
“…An estimated 10,000 physicians qualify to reenter practice each year after a period of clinical inactivity 13 . Most physicians seeking reentry do not seek additional training, especially if not required by state or medical specialty boards.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation